2009
DOI: 10.1111/j.1550-7408.2009.00427.x
|View full text |Cite
|
Sign up to set email alerts
|

Ketoconazole Inhibits the Growth and Development of Ichthyophonus sp. (Mesomycetozoa) In Vitro

Abstract: El artículo seleccionado no se encuentra disponible por ahora a texto completo por no haber sido facilitado todavía por el investigador a cargo del archivo del mismo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
4
1
Order By: Relevance
“…There were no clear differences between the 2 types of lipidic vehicles utilised (liposomes or emulsions), in terms of prevalence of infection. This contrasts with earlier data which indicate that in vitro cultures of Ichthyophonus are more sensitive to liposomated KZ formulations (Hontoria et al 2009). These differences could be due to inevitable variations in chemotherapeutant modes of action between in vivo and in vitro systems or to increased difficulties in targeting tissues with KZ, as Ich thyophonus spores tend to be surrounded by areas of granulomatous reaction or even encapsulated by layers of connective tissue (Franco-Sierra et al 1997).…”
Section: Experimental Treatmentscontrasting
confidence: 68%
See 3 more Smart Citations
“…There were no clear differences between the 2 types of lipidic vehicles utilised (liposomes or emulsions), in terms of prevalence of infection. This contrasts with earlier data which indicate that in vitro cultures of Ichthyophonus are more sensitive to liposomated KZ formulations (Hontoria et al 2009). These differences could be due to inevitable variations in chemotherapeutant modes of action between in vivo and in vitro systems or to increased difficulties in targeting tissues with KZ, as Ich thyophonus spores tend to be surrounded by areas of granulomatous reaction or even encapsulated by layers of connective tissue (Franco-Sierra et al 1997).…”
Section: Experimental Treatmentscontrasting
confidence: 68%
“…Recent in vitro studies (Hontoria et al 2009) confirmed the above-mentioned inhibitory effect of KZ on Ichthyophonus growth and endorsed its potential use in the treatment of ichthyophoniasis. These previously available data related to in vitro studies prompted us to conduct in vivo studies on the effect of KZ on ichhyophoniasis, using European sea bass Dicentrarchus labrax L. as a fish model.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…9) but has also been encountered in marine fish with mixed haplotype isolates 2 and in mullet (Mugilidae) from the Mediterranean Sea. 4 The opaleye in this study had no known exposure to living freshwater fish. Although they had access to some frozen freshwater fish (including river smelt, which was fed to puffins in the exhibit), freezing kills Ichthyophonus life stages, preventing transmission of infection.…”
mentioning
confidence: 99%